Rancangan Enterprise Architecture untuk Layanan Maintenance dan Logistik: Studi Kasus PT Berkah Industri Mesin Angkat (PT BIMA) - Iim Umamil Khoiri; Betty Purwandari; Riri Satria; Raden Trimanadi; Raden Trimanadi (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
PT Berkah Industri Mesin Angkat (PT BIMA), a subsidiary of a state-owned enterprise, operates 67 branches across Indonesia, providing engineering services, port equipment maintenance, spare parts procurement, and port civil engineering services. The company faces significant challenges, including suboptimal integration of information systems, fragmented operational monitoring processes, and reactive maintenance and data management practices. These conditions have resulted in inefficient operational performance and suboptimal managerial decision-making. This study aims to design an Enterprise Architecture (EA) aligned with the company's business needs to support the integration of business processes, information systems, and information technology for PT BIMA's maintenance services. The research employs a qualitative approach using the TOGAF ADM (Architecture Development Method) framework, with data collected through document studies and interviews. The scope is limited to Phase D (Technology Architecture), as this study represents the initial EA planning stage in a company that lacks formal architectural documentation. Data analysis was conducted using open coding to identify and categorize concepts derived from raw interview data. The findings propose four key innovations: an Integrated Maintenance Monitoring Dashboard, Data Warehouse & Business Intelligence, an Integrated Asset Management System, and a Mobile Maintenance Application. This EA design is expected to enhance operational efficiency, improve data integration across business units, enable real-time service monitoring, and support data-driven decision-making at PT BIMA.